Kerala's Industrial Backwardness: A Case of Path Dependence in Industrialization? - Jayan Jose Thomas (ISAS Background Brief No. 3 - Date: 15 May 2005, 2005)
The Indian State of Kerala presents a paradox of development, with its remarkable social achievements and relative industrial backwardness. This paper describes Kerala's industrial backwardness as due to a path dependent process of industrialization. A policy decision in the 1930s - marked by a priority for investments in chemicals-based industries and the identification of hydroelectricity as a potential basis for industrialization - continue to have implications for industrial growth in Kerala today. With the policy decision in the 1930s, industrial structure in Kerala came to be locked into a pattern that offered very little potential for inter-industry inter-linkages and industrial growth.